Alkoxyamine-mediated "living" radical polymerization: MS investigation of the early stages of styrene polymerization initiated by cumyl-TEISO - Cresidio, Salvacion P. (Animo Repository, 2001)
A new series of 1,1,3,3-tetraethylisoindoline-2-oxyl (TEISO)-based alkoxyamines was prepared. The half-lives for thermal dissociation indicated that the most sterically congested cumyl-TEISO alkoxymine had the greatest potential as an initiator for the polymerization of monomers at lower temperatures. The polymerization of styrene at 110 °C gave a linear evolution of Mn with conversion in the early stages. Further evidence for the "living" nature was given by the polydispersities of the polymers that remained low (Mw/Mn = 1.13-1.27) throughout the polymerization (up to 80% conversion). No polymer was formed for the styrene system in a reasonable time below 100 °C. High-performance liquid chromatographic/mass spectrometric investigations of the distribution of trapped oligomers containing one to nine monomer units formed at 60 °C revealed that the trapping of oligomeric cumyl-styryl radicals by TEISO is irreversible at this temperature. Methyl methacrylate polymerized with cumyl-TEISO at 60-70 °C, although the initial high rates of polymerization soon decreased to zero at low conversions (10-15%), and the high polydispersities (Mw/Mn = 1.42-1.73) indicated significant side reactions. © 2001 John Wiley & Sons, Inc.